MODEL PENGUKURAN AKUNTABILITAS KINERJA DPRD DALAM KONTEKS GOOD GOVERNANCE - Sadu Wasistiono (Jurnal Ilmu Pemerintahan Widya Praja, 2019)
Indonesia is one of the country which running biggest decentralization in the world, include transfer of authority, transfer of money, and moving government officials from central government to sub national government. There are three targets of decentralization i.e political, administrative, and social economy. One of political target of decentralization is make infrastructure and suprastructure of politic in local government more democratic and accountable. One of characteristic of good governance is accountable, and then more bigger and bigger transferring authority and money from central government to local government, must followed by accountability. But DPRD as local council have no model for accountability. Accountability of DPRD as political institutional is measuring by the functions, not only how to use the annually budget. Usually DPRD have four functions i.e budgetary, how to make local regulation, political controlling, and representative function. This paper is try to make model for measuring performance accountability of DPRD in good governance context.